SELF-EFFICACY IN SOLVING MATHEMATIC PROBLEMS BASED ON GENDER - Irianti, Nathasa Pramudita; Barr, Farah Dzil; Nurasiah, Lilis; Irsal, Nur Aliyyah (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
The purpose of this study is to examine how students' self-efficacy relates to and influences their gender-based mathematical problem-solving. 36 students taking an applied mathematics course are involved in this study, which uses a descriptive methodology. Test problems and a self-efficacy questionnaire are among the study tools utilized. The independent sample t-test is the data analysis technique used to evaluate gender-based differences in mathematical self-efficacy. Pearson correlation is used to examine the relationship between students' self-efficacy and their capacity to solve applied mathematics problems, and simple linear regression is used to assess how self-efficacy levels affect students' capacity for problem-solving. The results from the independent sample t-test indicate that there are no significant differences in mathematical self-efficacy between male and female students in the Applied Mathematics class. Additionally, there are also no significant differences between the problem-solving abilities of male and female students. Pearson correlation analysis shows a strong positive relationship between self-efficacy and the ability to solve mathematical problems. Furthermore, the results of simple linear regression confirm that self-efficacy has a substantial contribution (95.6%) to problem-solving abilities in mathematics. Other factors also play a role, but to a lesser extent